Generative Artificial Intelligence as an Adaptive Medium to Optimize Interactive Learning for Teachers at Public Special Schools - Kheyene Molekandella Boer; Nurliah Nurliah; Masna Wati; Muhammad Aidil Ilham; Latifa Latifa (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The rapid advancement of Generative Artificial Intelligence (GenAI) has transformed the global educational landscape; however, its implementation in Public Special Schools remains limited due to low digital competence and technological access gaps. This condition contributes to the continued dominance of conventional, teacher-centered instruction that lacks adaptability to diverse student needs. This community service research aimed to enhance teachers’ competence in utilizing GenAI as an adaptive medium to optimize interactive learning. The program was conducted through a two-day workshop at SLBN Pembina, East Kalimantan Province, involving 46 teachers from elementary, junior high, and senior high special education levels. The activities included the development of two instructional modules (“Smarter Teaching with ChatGPT” and “Creative Teaching with Canva”), pre- and post-tests, hands-on practice, individual assignments, and post-activity monitoring. The findings revealed a 28.20% increase in teachers’ understanding during the ChatGPT session and a 48.96% improvement during the Canva session. Classroom monitoring further indicated enhanced student engagement and enthusiasm when AI-based materials were implemented. The implications highlight that structured and contextual training can effectively bridge the digital divide in special education settings, strengthen teacher self-efficacy, and promote more personalized, interactive, and inclusive AI-enhanced learning practicesPerkembangan pesat Generative Artificial Intelligence (GenAI) telah mentransformasi lanskap pendidikan global, namun implementasinya di Sekolah Luar Biasa Negeri (SLBN) masih terbatas akibat rendahnya kompetensi digital dan kesenjangan akses teknologi. Kondisi ini berdampak pada masih dominannya metode pembelajaran konvensional yang kurang adaptif terhadap kebutuhan peserta didik berkebutuhan khusus. Penelitian pengabdian ini bertujuan untuk meningkatkan kompetensi guru dalam memanfaatkan GenAI sebagai media adaptif guna mengoptimalkan interactive learning. Metode pelaksanaan dilakukan melalui pendekatan pelatihan berbasis workshop selama dua hari di SLBN Pembina Provinsi Kalimantan Timur dengan melibatkan 46 guru dari jenjang SDLB, SMPLB, dan SMALB. Kegiatan meliputi penyusunan dua modul (“Mengajar Lebih Cerdas dengan ChatGPT” dan “Kreatif Mengajar dengan Canva”), pre-test dan post-test, praktik langsung, penugasan individu, serta monitoring pascakegiatan. Hasil penelitian menunjukkan peningkatan pemahaman guru sebesar 28,20% pada sesi ChatGPT dan 48,96% pada sesi Canva. Monitoring lapangan juga menunjukkan meningkatnya keterlibatan dan antusiasme siswa saat materi berbasis AI diterapkan di kelas. Implikasi kegiatan ini menegaskan bahwa pelatihan terstruktur dan kontekstual mampu menjembatani kesenjangan digital di sekolah khusus, memperkuat kepercayaan diri guru, serta mendorong implementasi pembelajaran yang lebih personal, interaktif, dan inklusif berbasis teknologi AI.